VALIDATION OF ACTIVE LEARNING SCALE IN ELEMENTARY SCHOOL BASED ON THE INDONESIAN TEACHER PERCEPTION - Laurens Kaluge; Yulianti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the validity and reliability of a measuring tool that reflects active learning in elementary schools, which is called the Active-Learning-in-Primary-School Scale (SPASD). The research was quantitative, which adheres to the idea of item-response- theory. The data used was secondary that was obtained from the Managing-Good-Practice-for- Basic-Education program, which was collected under the sponsorship of the European Commission based on five different provinces in Indonesia using a questionnaire developed under the coordination of UNICEF even though it has not been statistically validated. The sample of 1021 primary school teachers met the requirements for analysis. Exploratory and confirmatory factor analysis proves that there are several constructs. Seven valid dimensions were found namely training utilization, teaching planning, learning process, and evaluation, use of media, teacher professional satisfaction, and classroom climate. Some items were removed because they were not valid, even though all the hypothesized constructs remained valid and reliable. In conclusion, the tested scale was valid and reliable with a slight modification of the structure. It is recommended that the application of the constructs should bere-confirmed if it is applied in the context of different places, cultures, and school conditions.